2009
DOI: 10.1107/s0909049509016987
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral delivery of 5-iodo-2′-deoxyuridine in combination with synchrotron stereotactic radiation for the therapy of the F98 glioma

Abstract: Iodine-enhanced synchrotron stereotactic radiotherapy takes advantage of the radiation dose-enhancement produced by high-Z elements when irradiated with mono-energetic beams of synchrotron X-rays. In this study it has been investigated whether therapeutic efficacy could be improved using a thymidine analogue, 5-iodo-2'-deoxyuridine (IUdR), as a radiosentizing agent. IUdR was administered intracerebrally over six days to F98 glioma-bearing rats using Alzet osmotic pumps, beginning seven days after tumor implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Harrington et al (9) showed improvement in time to volume tripling of KB xenographs in mice receiving five fractions at 3 Gy/fraction using pegylated liposomal IUdR (PLIUdR) + 137 Cs gamma rays (34 days), as compared to PLIUdR (9 days) or 137 Cs gamma rays (19 days) alone. By contrast, Rousseau et al (10) showed no significant difference in median survival of rats with F98 glioma that received 15 Gy in one fraction when using IUdR + 50 keV photons (46 days) and 50 keV photons alone (44 days). More recently, combinations of conventional radiation with the less toxic prodrug 5-iodo-2-pyrimidinone-2'-deoxyribose (IPdR) have been found to significantly inhibit growth of human colorectal and glioblastoma xenografts, over the inhibition due to radiation alone (6,11).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Harrington et al (9) showed improvement in time to volume tripling of KB xenographs in mice receiving five fractions at 3 Gy/fraction using pegylated liposomal IUdR (PLIUdR) + 137 Cs gamma rays (34 days), as compared to PLIUdR (9 days) or 137 Cs gamma rays (19 days) alone. By contrast, Rousseau et al (10) showed no significant difference in median survival of rats with F98 glioma that received 15 Gy in one fraction when using IUdR + 50 keV photons (46 days) and 50 keV photons alone (44 days). More recently, combinations of conventional radiation with the less toxic prodrug 5-iodo-2-pyrimidinone-2'-deoxyribose (IPdR) have been found to significantly inhibit growth of human colorectal and glioblastoma xenografts, over the inhibition due to radiation alone (6,11).…”
Section: Introductionmentioning
confidence: 91%
“…As confidence intervals for the data were needed, all data points were included in the non-weighted analysis. The SER 10 values were calculated, and standard errors (1s) for SER 10 values computed by propagating errors in D 10 , dose for 10% SF. Standard errors in D 10 were estimated as one half of the dose range spanned by the 95% confidence interval (2s) for the LQ fits to the measured data.…”
Section: Clonogenic Survival Assay and Data Analysismentioning
confidence: 99%
“…injection of iodine contrast medium, which demonstrated the method to be safe and potentially beneficial [15]. Monochromatic synchrotron x-rays are currently being considered for iodine-enhanced treatment of brain tumors [1618]. However, the difficulty with the low-molecular-weight iodine agents involves achieving a high enough concentration in tumors [16].…”
mentioning
confidence: 99%
“…Recently, Rousseau and coworkers used 5-iodo-2 0 -deoxyuridine (IUdR) as a radiosensitizer in a F98 glioma-bearing rat model and in association with synchrotron X-rays. Although treated rats survived longer in comparison with the untreated group, the combination of treatments did not significantly improve survival compared with X-irradiation or chemotherapy alone [151]. Hence, the development of iodine microspheres or nanoparticles may be useful in that context [152] (Table 2).…”
Section: Nanomedicines and Factors Influencing Dose Deposition Iodinementioning
confidence: 96%